The The Impact of Learning from Home (LFH) during Covid-19 Pandemic on Students' Learning Loss - Amiruddin Hadi Wibowo (Universitas Muhammadiyah Gresik, 2022)
This paper aims to investigate the phenomena of learning loss during Learning from home in the Indonesian education system and offer solutions to prevent more severe learning loss. It begins with analyzing the implementation of LFH in the Indonesian educational system and demonstrates the existence of learning loss among LFH students. It then provides a solution to prevent learning loss. Thus, it concludes with a recommendation to the stakeholders to collaborate in order to implement the solution.